Risk Factors and Outcomes for Patients With Follicular Lymphoma Who Had Histologic Transformation After Response to First-Line Immunochemotherapy in the PRIMA Trial - Sarkozy, Clémentine; Trneny, Marek; Xerri, Luc; Wickham, Nick; Feugier, Pierre; Leppa, Sirpa; Brice, Pauline; Soubeyran, Pierre; Gomes Da Silva, Maria; Mounier, Christiane; Offner, Fritz; Dupuis, Jehan; et al. (Journal of clinical oncology, 2016)
PURPOSE: To study the outcome of histologic transformation (HT) in a large prospective cohort of patients with follicular lymphoma (FL) who previously responded to immunochemotherapy. PATIENTS AND METHODS: After a median 6-year follow-up of 1,018 randomly assigned patients from the PRIMA trial, disease progression was observed in 463 patients, 194 of whom had histologic documentation. RESULTS: Forty patients had histology consistent with HT, and 154 had untransformed FL (median time to recurrence, 9.6 v 22.8 months, respectively; P = .018). Thirty-seven percent of biopsies performed during the first year of follow-up showed HT corresponding to 58% of all HTs. Altered performance status, anemia, high lactate dehydrogenase level, "B" symptoms, histologic grade 3a, and high Follicular Lymphoma International Prognostic Index scores at diagnosis were identified as HT risk factors. Response (complete v partial) to immunochemotherapy or rituximab maintenance had no impact on the risk of HT. After salvage treatment, patients with HT had less frequent complete response (50.3% v 67.4%; P = .03) and more disease progression (28.2% v 9.6%; P < .001) than patients without HT. Estimated overall survival for the patients with HT was poorer (median, 3.8 v 6.4 years; hazard ratio, 3.9; 95% CI, 2.2 to 6.9). Autologous stem cell transplantation improved the outcomes of patients with HT (median overall survival, not reached v 1.7 years) but not of patients with persistent FL histology. CONCLUSION: HT in patients with FL who previously responded to immunochemotherapy is an early event associated with a poor outcome that may deserve intensive salvage with autologous stem cell transplantation. These data emphasize the necessity for biopsy at the first recurrence of FL.
Keywords: Stem Cell Transplantation; dospělí; záchranná terapie; Female; Adult; výsledek terapie; ženské pohlaví; Neoplasm Recurrence, Local; biopsie; lidé; transplantace kmenových buněk; Lymphoma, Follicular; Rituximab; Salvage Therapy; Treatment Outcome; Aged, 80 and over; kohortové studie; Risk Factors; Cohort Studies; prospektivní studie; Male; progrese nemoci; Aged; Prospective Studies; Biopsy; rituximab; Disease Progression; lokální recidiva nádoru; rizikové faktory; folikulární lymfom; lidé středního věku; senioři nad 80 let; senioři; mužské pohlaví; Middle Aged; Humans